Wavelet correlation between subjects: A time-scale data driven analysis for brain mapping using fMRI - Lessa, Patricia S.; Sato, João R.; Cardoso, Elisson F.; Neto, Carlos G.; Valadares, Ana Paula; Amaro, Edson (Journal of neuroscience methods, 2011)
▶ Development of data-drive methods for brain mapping. ▶ Wavelet correlations as alternatives to conventional GLM analysis. ▶ Wavelet correlations show greater sensitivity compared to GLM. Functional magnetic resonance imaging (fMRI) based on BOLD signal has been used to indirectly measure the local neural activity induced by cognitive tasks or stimulation. Most fMRI data analysis is carried out using the general linear model (GLM), a statistical approach which predicts the changes in the observed BOLD response based on an expected hemodynamic response function (HRF). In cases when the task is cognitively complex or in cases of diseases, variations in shape and/or delay may reduce the reliability of results. A novel exploratory method using fMRI data, which attempts to discriminate between neurophysiological signals induced by the stimulation protocol from artifacts or other confounding factors, is introduced in this paper. This new method is based on the fusion between correlation analysis and the discrete wavelet transform, to identify similarities in the time course of the BOLD signal in a group of volunteers. We illustrate the usefulness of this approach by analyzing fMRI data from normal subjects presented with standardized human face pictures expressing different degrees of sadness. The results show that the proposed wavelet correlation analysis has greater statistical power than conventional GLM or time domain intersubject correlation analysis.